A PROSPECTIVE STUDY ON SURGICAL STIE INFECTIONS AT A TERTIARY CARE CENTRE (Asian Journal of Medical Research and Health Sciences, 2023)
Background: Wound infection is tissue invasion by micro organisms after disruption of systemic and local host de-fenses, causing lymphangitis, cellulitis, abscesses, bacteremia. Aims &objectives: This prospective study aims at estimating incidence of surgical site infections (SSI) and risk factors of SSIs in general surgical wards at a tertiary care center. Methods: Study design: Prospective study. Source of study: General Surgery Inpatients. Duration Of study: One and half year starting from December 2020 to May 2022. Number of patients:200. Inclusion criteria- Pa-tients who developed surgical site infection following either elective or non-traumatic emergency surgery. Age>18years, Patients giving informed consent. Exclusion criteria: Pregnant women, Age